2022
DOI: 10.1002/cssc.202200075
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Electrochemical Activation of V2O3@C Cathode for High‐Performance Zinc‐Ion Batteries in Water‐in‐Salt Electrolyte

Abstract: Aqueous Zn-ion batteries (ZIBs), with the advantages of low cost, high safety, and high capacity, have great potential for application in grid energy storage and wearable flexible devices. However, their commercial application is still restricted by their inferior long-term cycling stability, Zn dendrite formation, and the decomposition of aqueous electrolyte. In this study, a Zn j Zn(CF 3 SO 3 ) 2 + LiTFSI j V 2 O 3 @C cell is constructed to address the above issues. The V 2 O 3 @C electrode can be fully oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…The WiS electrolyte exhibited a lower contact angle than diluted electrolyte (ZnSO 4 and Zn(OTf) 2 ), suggesting the WiS electrolyte greatly improved the V 2 O 3 @C cathode wettability and facilitated Zn 2+ -ion transfer kinetics (Figure 7c). 80 In addition, the redox peaks were shifted to higher potential than those for diluted electrolyte. 80 Moreover, it is evident that the highly concentrated WiS electrolyte based on 21 M LiTFSI + 0.43 M Zn(OTf) 2 , which contained almost no free water molecules, exhibited comparatively lower electrochemical performance than 6 M LiTFSI + 3 M Zn(OTf) 2 WiS electrolyte.…”
Section: Electrolyte Engineering Strategies To Mitigate Undesired Sid...mentioning
confidence: 98%
See 3 more Smart Citations
“…The WiS electrolyte exhibited a lower contact angle than diluted electrolyte (ZnSO 4 and Zn(OTf) 2 ), suggesting the WiS electrolyte greatly improved the V 2 O 3 @C cathode wettability and facilitated Zn 2+ -ion transfer kinetics (Figure 7c). 80 In addition, the redox peaks were shifted to higher potential than those for diluted electrolyte. 80 Moreover, it is evident that the highly concentrated WiS electrolyte based on 21 M LiTFSI + 0.43 M Zn(OTf) 2 , which contained almost no free water molecules, exhibited comparatively lower electrochemical performance than 6 M LiTFSI + 3 M Zn(OTf) 2 WiS electrolyte.…”
Section: Electrolyte Engineering Strategies To Mitigate Undesired Sid...mentioning
confidence: 98%
“…80 In addition, the redox peaks were shifted to higher potential than those for diluted electrolyte. 80 Moreover, it is evident that the highly concentrated WiS electrolyte based on 21 M LiTFSI + 0.43 M Zn(OTf) 2 , which contained almost no free water molecules, exhibited comparatively lower electrochemical performance than 6 M LiTFSI + 3 M Zn(OTf) 2 WiS electrolyte. This result suggested that an appropriate amount of free water molecules is required in electrolyte to exhibit high electrochemical performance.…”
Section: Electrolyte Engineering Strategies To Mitigate Undesired Sid...mentioning
confidence: 98%
See 2 more Smart Citations
“…Among them, V 2 O 5 with various morphology and their composites has been widely explored as cathode for ZIBs. [28][29][30][31] Both orthorhombic V 2 O 5 (α-V 2 O 5 ) and bilayered V 2 O 5 (V 2 O 5 nH 2 O) have typical layered structures (Figure 3a,b) with adjacent layers combined by Van der Waals force. [32,33] α-V 2 O 5 possesses a layer spacing of 5.8 Å, which is large enough for storing Zn 2+ and V 2 O 5 nH 2 O usually has larger layer spacing with crystal water in the interlayer.…”
Section: Classification Of V-based Cathodesmentioning
confidence: 99%